Can senior executive characteristics improve carbon emission performance? Evidence from China - Liu, Xun; He, Mengqi; Zhang, Shaoyong; Zhuang, Zhao; Cai, Cheng (Frontiers in Ecology and Evolution, 2023)
As the backbone of China's market economy, controlling the corporate carbon emissions and reducing envi-ronmental pollution are important in China at this stage. This study aims to investigate the relationship between the characteristics of senior managers and the carbon emission performance of enterprises. The empirical study uses panel data in high-emission industries in China's A-share from 2014 to 2017. The results show that the natural age, education level, and professional background of senior managers in high emission enterprises are negatively related to the carbon emission performance of enterprises, but in the case of large enterprises, there is no strong relationship between the natural age of executives and carbon emission performance, while pro-fessional background and education level are negatively related to carbon emission performance, and natural age is significantly related to carbon emission performance in small and medium enterprises. In the regional classification of enterprises, the natural age and professional background of core executives of high-emitting enterprises in the eastern region are negatively correlated with carbon emission performance, while the profes-sional background of core executives of high-emitting enterprises in the central and western regions are posi-tively correlated with carbon emission performance, while the natural age and educational level of executives are negatively correlated with carbon emission performance. To measure the carbon emission performance of enterprise, the paper designs the balanced scorecard evaluation system (CEP); meanwhile, the paper innova-tively classifies and cuts the sample companies into overall size and distribution area, analyzing carbon per-formance and executive characteristics from two perspectives. It provides certain suggestions and counter-measures for companies in China, especially in high-emission industries, it’s helpful in reducing pollution.